2012
DOI: 10.1007/s10661-012-2835-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of possible health risks of heavy metals by consumption of foodstuffs available in the central market of Rajshahi City, Bangladesh

Abstract: Considering the human health risk due to the consumption of foodstuffs, the concentrations of heavy metals (lead, manganese, chromium, cadmium, and arsenic) are investigated in vegetables, fruits, and fish species collected from the central market (called Shaheb Bazar) of Rajshahi City, Bangladesh. The foodstuffs examined for metal constituents are the basis of human nutrition in the study area. The highest concentrations of Mn and As in vegetables (onion and pointed gourd, respectively), Cr and Cd in fruits (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(126 citation statements)
references
References 44 publications
12
107
6
1
Order By: Relevance
“…THQ values similar to this study were obtained in a research analysing the arsenic concentration in fish bought from markets in Bangladesh (Saha & Zaman 2013). Moreover, the inorganic arsenic THQ value from consumption of marine cultured fish in China (0.05) was found to be the critical level (Onsanit et al, 2010).…”
Section: Resultssupporting
confidence: 84%
“…THQ values similar to this study were obtained in a research analysing the arsenic concentration in fish bought from markets in Bangladesh (Saha & Zaman 2013). Moreover, the inorganic arsenic THQ value from consumption of marine cultured fish in China (0.05) was found to be the critical level (Onsanit et al, 2010).…”
Section: Resultssupporting
confidence: 84%
“…A study with fish and water of Turag river found high lead in water samples (0.1169±0.041 ppm) (Maximum allowable concentration is 0.05 ppm) and "Lia fish" (Lamellidens corrianus) (3.8656 ± 1.041 mg/kg) (FAO standards-0.10 mg/kg) (Mandal and Ahmed, 2013). Another study with samples from central market of Rajshahi, Bangladesh found high Pb in fish "Major carp" (Catla catla) (Saha and Zaman, 2013).…”
Section: Contamination Of Foods In Bangladeshmentioning
confidence: 99%
“…Researchers such as Saha and Zaman (2012) have revealed that there could be an interactive and/or additive effects upon the exposure of two or more pollutants. This could lead to a combined health index.…”
Section: Risk Assessment Hazard Indexmentioning
confidence: 99%